Parental Education and Early Marriage Among Young Women : Pendidikan Orang Tua dan Pernikahan Dini di Kalangan Perempuan Muda - Putri, Rischa Dwi; Kusumawardani, Paramitha Amelia; Azizah, Nurul; Widowati, Hesty (Indonesian Journal on Health Science and Medicine, 2025)
General Background: Early marriage remains a significant public health and social issue, often occurring before individuals reach the legal minimum age. Specific Background: Internal determinants, particularly knowledge, individual education, and parental education, have been cited as factors influencing early marriage, yet empirical evidence is still inconsistent. Knowledge Gap: Limited studies in Indonesia have explored which internal factors have the strongest association with early marriage practices. Aims: This study aimed to analyze the relationship between internal factors and early marriage in Curahkalong village, Jember district. Results: A cross-sectional analytic study was conducted with 38 married women selected by purposive sampling. Data were collected using questionnaires and analyzed with the Chi-square test at a significance level of α < 0.05. Findings showed a significant relationship between parental education and early marriage (p = 0.003), while no significant relationship was found for individual knowledge (p = 1.000) or respondent education (p = 0.180). Novelty: This research highlights parental education as the primary internal factor related to early marriage, while individual knowledge and education were not significant predictors. Implications: The findings suggest that parental involvement and educational background are critical in preventing early marriage, emphasizing the need for family-based reproductive health education programs. Highlights: Parental education strongly correlates with early marriage. Individual knowledge shows no significant association. Family-based interventions are essential for prevention. Keywords: Early Marriage, Adolescents, Parental Education, Knowledge, Internal Factors